Der dialogisch-konfessionelle Religionsunterricht (dk:RU) in Österreich: Herausforderungen und Anforderungen an die Lehrerinnen- und Lehrerprofessionalität in dialogischen Settings - Panzer, Astrid (Österreichisches Religionspädagogisches Forum, 2024)
While society today experiences religious pluralization and secularization, religious education remains predominantly organized in a mono-confessional manner, which raises concerns. Austria presents an alternative approach to religious education known as dk:RU (confessional cooperation in religious education), which views religious diversity as an educational opportunity. However, insufficient attention has been given to the significant challenges faced by teachers and the required professional competencies in this context. Hence, this master thesis concentrates on teacher professionalism, the associated challenges, and the necessary qualifications for teaching mixed-denominational learning groups.